2016
DOI: 10.5664/jcsm.5390
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Stimulation for Obstructive Sleep Apnea: Self-Reported Outcomes at 24 Months

Abstract: Objectives:To evaluate the long-term (24-mo) effect of cranial nerve upper airway stimulation (UAS) therapy on patient-centered obstructive sleep apnea (OSA) outcome measures. Methods: Prospective, multicenter, cohort study of 126 patients with moderate to severe OSA who had difficulty adhering to positive pressure therapy and received the surgically implanted UAS system. Outcomes were measured at baseline and postoperatively at 12 mo and 24 mo, and included self-and bedpartner-report of snoring intensity, Epw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 25 publications
(26 reference statements)
1
84
0
3
Order By: Relevance
“…Additional studies of the STAR cohort showed maintenance of these outcomes at 18, 24, and 36 months. [6][7][8][9] Two case series with chart reviews have been published since, with smaller cohorts of patients that have been consistent with the results seen in the STAR trials. Kent et al 10 reviewed their series of 20 patients and found improvement in postoperative AHI and ESS from 33.3 to 5.1 and 10.3 to 6 respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Additional studies of the STAR cohort showed maintenance of these outcomes at 18, 24, and 36 months. [6][7][8][9] Two case series with chart reviews have been published since, with smaller cohorts of patients that have been consistent with the results seen in the STAR trials. Kent et al 10 reviewed their series of 20 patients and found improvement in postoperative AHI and ESS from 33.3 to 5.1 and 10.3 to 6 respectively.…”
Section: Discussionmentioning
confidence: 77%
“…For example, complete concentric collapse of the palate in OSA patients predicts failure to respond to upper airway neuro-stimulation therapy [24]. Although the biological underpinnings of this OSA feature are not fully understood, meaningful benefits can accrue from using this phenotype to augment clinical trial design [15] and patient care [25]. The definition also provides a basis for deeper characterization of physiological or molecular mechanistic investigations.…”
Section: Osa Phenotype a Definitionmentioning
confidence: 99%
“…The Inspire-sponsored FDA Phase III Stimulation Therapy for Apnea Reduction (the STAR trial) has to date the most information on outcomes with this therapy: safety and efficacy 1921 . The STAR trial was a prospective cohort study which enrolled 126 CPAP-intolerant OSA patients, all of whom had activation of the therapy about 1 month after implantation.…”
Section: Beyond the 12-months Of The Star Trialmentioning
confidence: 99%
“…There is probably a need a PSG sometime after implant (1–2 months) to examine the effect of stimulation on event type in all positions and in all stages of sleep, as well as to show improvements in oxygen saturation and heart rate by sleep state. However, management at follow-up can be managed by home sleep testing, portable studies of cardiopulmonary function over time without sleep, as shown in post-approval studies 19, 53 .…”
Section: Management Experiencesmentioning
confidence: 99%